The Effectiveness of Flashcard Media Using a Constructivist Approach for Learning to Use Spelling in Writing Descriptive Texts - Subandiyono; Iis Ristiani (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to determine: 1) the results of the pre-test of the ability to use Enhanced Spelling (EYD); 2) the results of the post-test of the ability to use EYD in learning descriptive text skills using a constructivist approach in flashcard media; 3) the effectiveness of the constructivist approach through flashcard media in learning the ability to use EYD in descriptive text. This study uses quantitative descriptive which took place in the odd semester of the 2025/2026 academic year at SMK Ar-Rahman Cianjur. The population of this study was 19 students of grade XI who took the pre-test and learning the ability to use EYD in writing descriptive texts using a constructivist approach via flashcard media. The sample was selected 17 students based on Slavin's formula. Before the learning began, the population members did a pre-test of writing descriptions based on EYD and a post-test. After that, the pre-test data was analyzed to be used as a basis for learning. After learning, the sample members took the post-test. Data were collected using a test instrument that was compiled objectively and systematically based on test specifications. The research data were analyzed using parametric inferential statistical procedures, namely one-sample t-test and paired-sample t-test. The results of the study: 1) the pre-test results of the ability to use Enhanced Spelling only reached a mean of 23.46 or a standard score of 64.64; 2) the post-test results of the ability to use Enhanced Spelling in learning descriptive text skills using the flash card method reached a mean of 36.03 or a standard score of 90.07; 3) the flash card method is effective in learning the ability to use Enhanced Spelling in descriptive text.